Managing Reductions in Aid Inflows : Assessing Policy Choices in Haiti - Moldovan, Ioana (IMF Working Papers; Working Paper ;, 2018)
A low-income country such as Haiti that confronts an environment of diminishing aid inflows must assess tradeoffs among the available policy options: spending cuts, monetization, sales of debt, or use of foreign reserves. To provide the analytical tools for this task, the paper draws from a set of DSGE models recently developed to evaluate policy choices in low-income countries for which external aid flows represent an important revenue source. Two simplified stylized variations of the main model are used to gain intuition and initially assess the trdeaoffs. Subsequenctly a full-scale small open economy DSGE model, calibrated to match conditions in Haiti and in similar low-income countries, is employed. Several key results are common to all model versions. While sales of foreign exchange reserves can compensate for the loss of aid inflows, this strategy is not sustainable. The remaining policy choices entail larger welfare costs, involving lower consumption levels and real depreciation. The results suggest that a mixture of spending cuts and depreciation is the best strategy, when use of foreign reserves is constrained.